ENVIRONMENTAL COMPETENCE OF A GEOGRAPHY TEACHER -AS A GUARANTEE OF EDUCATIONAL EFFECTIVENESS (Academia Science Repository, 2023)
Today, a lot of attention is paid to the improvement of the educational system by our state. Nevertheless, it is no secret that in the educational process, the interest of students in acquiring knowledge is becoming a serious problem. Humanity has long been interested in the question of knowing and studying the world in which it lives. In fact, this is mainly given by geography education. In particular, geography is a primary educational discipline aimed at providing information to form a complete picture of the planet in which humanity lives, that is, the Earth. It occupies a special place within the system of all sciences. Because always the nature of the place where a person's life lives itself, which is closely related to the environment, has been formed on the basis of various processes. The importance of geography is that it provides the most necessary natural, socio-economic conditions of a person. The study of this science changes the scientific worldview of students, makes them aware of the surrounding events. Educates students in a responsible attitude to the environment and develops their intellectual potential.